Tanggung Jawab Negara Terhadap Pencemaran Laut - Ema Septaria; Amelia Ananda Hardiansyah; Putri Girana Ratu Pelangi; Azzura Nailah (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Marine pollution caused by human activities has led to extensive damage to maritime ecosystems, thus requiring comprehensive state responsibility to protect them. This research is urgent to identify the gap between marine protection legal regulations and their practical implementation. The method used is normative juridical research with a descriptive-analytical approach to related legislation. The results show that state responsibility is manifested through preventive measures, law enforcement, and environmental restoration. However, this implementation is hindered by weak supervision, overlapping authorities between central and regional governments, and minimal public participation. Therefore, a transformation of the state responsibility model is required through inter-agency policy integration, strengthening technology-based supervision, implementing strict liability principles, and involving coastal communities to achieve sustainable marine conservation.